A eficácia na execução do planejamento estratégico no poder judiciário do Rio Grande do Norte - Diogo Neto, José André (2013)
This paper presents an analysis of the current strategic plan of the Judiciary of Rio Grande do Norte emphasizing the evaluation of strategic indicators verifying the effectiveness in implementation, since the implementation of the Balanced Scorecard as a tool for performance evaluation of strategic management. The research presents the strategy map and the evaluation indices of strategic performance reporting on the effectiveness. After literature review and documentary, is making the measurement of indicators that are treated from the standpoint of an exploratory and descriptive in strategic planning used by the judiciary Potiguar. The problem was evaluated qualitatively and quantitatively using statistical techniques for data analysis comparing them between Judiciaries of Brazilian States. With respect to data collection was used performance indicators extracted from the data of Justice in Numbers provided by CNJ the period from 2004 to 2011, and the information sought in the Sector Strategic Planning TJ / RN. The main results of this study are as follows: Acquisition of insight into what level is the strategic planning of the judiciary of Rio Grande do Norte and the evolution of its performance indicators comparing them with the states of RS, CE, SE and the National Judiciary